The Effect of E-service quality and Brand image on Interests in Reusing Bibit Application - Gustyantoro, Ilham; Matoati, Rindang (Universitas Nahdlatul Ulama Sidoarjo, 2023)
The development of globalization has made all activities inseparable from technological assistance, including the digital investment sector. The increasing number of investors have made various digital investment applications compete to find users by improving the quality of service and brand image. The purpose of this studywas to analyze the effect of e-service qualityand brand image on the intention to reuse the Bibit application. This research was conducted in the Jabodetabek area using a quantitative method. The sample studied was Bibit application users in Jabodetabek and aged between 17-30 years as many as 160 people selected using a voluntary sampling technique. The data processing method uses SEM-PLS with the Smart PLS application 3. The results show that there was a positive and significant effect of e-service quality and brand image on the interest in reusing the Bibit application. others and can add other variables such as promotions and ease of use to interest in reusing Bibit